Engineering NK Cells for CAR Therapy—Recent Advances in Gene Transfer Methodology - Schmidt, Paula; Raftery, Martin J.; Pecher, Gabriele (Frontiers in Immunology, 2021)
The development of chimeric antigen receptor (CAR) T cell therapy has introduced a new and effective strategy to guide and promote the immune response against tumours in the clinic. More recently, in an attempt to enhance its utility, this method has been expanded to novel cell types. One of the more successful variants has proven to be the expression of CARs in natural killer (NK) cells (CAR-NK). Gene engineering NK cells to express an exogenous CAR receptor allows the innate anti-tumour ability of NK cells to be harnessed and directed against a target tumor antigen. In addition, the biology of NK cells allows the development of an allogeneic cell therapeutic product useable between most or all patient haplotypes. NK cells cause little or no graft verses host disease (GvHD) and are therefore suitable for development of an “off the shelf” therapeutic product. Initial trials have also shown that CAR-NK cells rarely cause cytokine release syndrome. However, despite their potential NK cells have proven to be difficult to engineer, with high sensitivity to apoptosis and low levels of gene expression. The creation of optimised methods to introduce genes into NK cells will promote the widespread application of CAR-NK into research laboratories and the clinic.